2016
DOI: 10.1186/s12968-017-0331-0
|View full text |Cite
|
Sign up to set email alerts
|

Proximal aortic stiffening in Turner patients may be present before dilation can be detected: a segmental functional MRI study

Abstract: BackgroundTo study segmental structural and functional aortic properties in Turner syndrome (TS) patients. Aortic abnormalities contribute to increased morbidity and mortality of women with Turner syndrome. Cardiovascular magnetic resonance (CMR) allows segmental study of aortic elastic properties.MethodWe performed Pulse Wave Velocity (PWV) and distensibility measurements using CMR of the thoracic and abdominal aorta in 55 TS-patients, aged 13-59y, and in a control population (n = 38;12-58y). We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
1
20
1
Order By: Relevance
“…Likewise, it is possible that the observed abnormalities of aortic distensibility are influenced by different blood flow profiles that has been demonstrated in Turner Syndrome, especially when BAV or CoA is present [43]. Contrary to the present study, a recent study of Turner Syndrome women found reduced aortic distensibility when BAV was present, which may possibly be due differences in the Turner Syndrome populations studied [44]. Here, we also show that the mean aortic area is similar or even slightly smaller (aortic arch) compared with controls, a difference that vanished after adjustment for BSA, but that the variability in aortic area is much larger, illustrated by the very wide range.…”
Section: Discussioncontrasting
confidence: 76%
“…Likewise, it is possible that the observed abnormalities of aortic distensibility are influenced by different blood flow profiles that has been demonstrated in Turner Syndrome, especially when BAV or CoA is present [43]. Contrary to the present study, a recent study of Turner Syndrome women found reduced aortic distensibility when BAV was present, which may possibly be due differences in the Turner Syndrome populations studied [44]. Here, we also show that the mean aortic area is similar or even slightly smaller (aortic arch) compared with controls, a difference that vanished after adjustment for BSA, but that the variability in aortic area is much larger, illustrated by the very wide range.…”
Section: Discussioncontrasting
confidence: 76%
“…Another study showing pathological elasticity levels in TS children independent of their aortic valve morphology [ 24 ] excluded adolescents due to a suspected negative influence of HRT as well as children below 6 years of age because of lesser cooperation, presenting a study population of only 15 patients. The same group presented an MRI study verifying these findings in a bigger study cohort, but including adult patients in a great amount as well [ 25 ]. Therefore, our study represents a more complete and greater cohort of children and adolescents.…”
Section: Discussionmentioning
confidence: 83%
“…Others have also investigated whether the presence of BAV can explain the increased aortic stiffness in patients with TS but the results are contradictory. Two studies 8,23 showed reduced ascending aortic distensibility and increased AA-PWV independently of the presence of BAV, while Devos et al 9 showed that only patients with BAV have a reduced ascending aortic distensibility. Our results are more in line with the first study, since we found no effect of BAV on stiffness.…”
Section: Discussionmentioning
confidence: 99%